Sustainable techniques used in food preparation | Técnicas sustentáveis ??utilizadas na preparação de alimentos - Padilha, Maria do Rosário de Fátima; Shinohara, Neide Kazue Sakugawa; Machado, José; Macedo, Indira Maria Estolano; Ferreira, Eron; Matsumoto, Masayoshi (Revista Geama, 2017)
In the globe, in the 21st century, millions of people are in malnutrition. In parallel, in the different food production units, as well as in the domestic environment, large losses occur from production to consumption. Studies have been conducted to minimize this serious scenario, which profoundly undermines sustainability and worsens the situation of vulnerable populations. The globalized world allows the contact and exchange of different food experiences and, therefore, the possibility of adopting sustainable culinary techniques. This work aimed to insert in some preparations the traditional and secular knowledge of some cultures, minimizing food waste that is despised by the majority of the population. For this purpose, watermelon waste (Citrullus lanatus spp) were used, using bleaching techniques and the improvement of the palatability with the addition of the bittersweet sauce enriched with umami flavor obtained through the incorporation of the Dashi broth.